Social Enterprises with the Poor as Primary Stakeholders: Responding to State and Market Failures in the South - Dacanay, Marie Lisa (Archīum Ateneo, 2013)
This paper presents a framework for understanding how social enterprises engage the poor and address poverty, a pressing global problem of the 21st century. It introduces social enterprises with the poor as primary stakeholders or SEPPS as a conceptual construct of a major type of social enterprise. SEPPS are characterized as responses to the failure of state and market institutions to serve the needs of the poor in developing countries or the South. Using case-based theory building as methodology, the paper presents three models of stakeholder engagement among social enterprises with the poor as primary stakeholders or SEPPS, namely control, collaboration and empowerment. The paper contributes to social entrepreneurship and stakeholder theory by developing propositions about the power and limitations of these three models in bringing about social inclusion and poverty reduction. While needing to be tested in a broader sample of SEPPS, these propositions are suggested to be applicable in the South or developing countries other than the Philippines where the empirical study was undertaken. In these countries, systemic poverty and inequality are exacerbated by the failure of state and market institutions to address the needs of the poor. Amidst such failure of state and market institutions in the South, the cases indicate that development institutions and solidarity markets in the North have served as critical enabling stakeholders of SEPPS. This indicates that SEPPS may be conceived as a global social enterprise model catalyzing South-North cooperation for poverty reduction.